CÁC THÀNH TẠO PHUN TRÀO VÀ XÂM NHẬP MESOZOI MUỘN TUYẾN A LƯỚI - ĐẮK RÔNG - Dũng, Lê Tiến; Anh, Phạm Thị Vân; Bản, Tô Xuân (Vietnam Journal of Earth Sciences, 2017)
Dackrong-Aluoi Volcanic line, West of Quang Tri and Thua Thien-Hue provinces, includes basalt, andesite, dacite, riolite and granite-porphyritic granophyritic shallow intrusive rocks. According to geological and petrological characteristics, they belong to effusive-explosivefacie, truly volcanic and hypabyssall facie o ffracture type of early Cretaceous age. In chemical aspect, the rocks form high potassium calc-alkal ine series in the activecontinental margin of Andes Type. Volcanic suffered strong hydrothermal metamorphosed profilitisation, bersitisation and argilitisation that related to silver-gold and polymetal mineralization. Small intrusive bodies and light color porphyritic granite Dikes which are strongly weathered, related to kaolinite deposits with high quality and medium size.